Impacto da Utilização de Pavimentação Permeável em Áreas Urbanas na Recuperação de Bacias Hidrográficas - Santos, Cristiano de Assumpção (2016)
Urbanization and the disorderly occupation of cities have created many environmental problems, ranging from floods to climate change in large urban centers. Among the causes of these occurrences is mainly soil sealing in cities, that occurs by interference and man's need to use more space. The more waterproofed the surface of urban areas, higher runoff, and this, in turn, due to the adopted public politics and the lack of planning, are transferred to adjacent watersheds, causing, these problems such as floods and silting of rivers. The impermeabilized surfaces end up affording a smaller charge of watersheds, transferring to other river basins the amount of water that it should be restored in the region, that way impair the recovery of the basins where the percolations occur. This study is a comparison between two existing technologies in commercially known market as "paver" and "draining floor", and point which of these can help in the recovery of watersheds and, consequently, reduce the problems caused by surface runoff in urban areas. To reach the result precipitations were simulated using a sprinkler infiltrometer in intensities corresponding to 45mm.h-1, 60mm.h-1 and 90mm.h-1, and occurred in lysimeters where the coverages match the public walks characteristics using the technologies to be analyzed as ground cover. This experiment showed that the permeable concrete parts (draining floor) and concrete parts gaskets extended (paver) has percolation rate likened to grass cover and thus can be used as technologies for water infiltration into the soil aiding in the recovery of watersheds in urban areas